1993
DOI: 10.1021/je00011a014
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of anthracene in binary alkane + 1-propanol and alkane + 1-butanol solvent mixtures

Abstract: Experimental solubilities are reported for anthracene dissolved in 12 binary mixtures containing l-propanol or l-butanol with hexane, heptane, octane, cyclohexane, methylcyclohexane, and 2,2,4-trimethylpentane at 25 OC. Results of these measurements are used to test two mathematical representations based upon the combined nearly ideal binary solvent (NIBS)/Redlich-Kister equation and modified Wilson model. For the systems studied, the combined NIBWRedlich-Kister equation was found to provide the better mathema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 5 publications
1
27
0
Order By: Relevance
“…The various S i "curve-fit" parameters can be evaluated via least-squares analysis. Published papers (Zvaigzne et al, 1993;Zvaigzne and Acree, 1994; have reported the calculated S i parameters for anthracene dissolved in eight of the nine sub-binary solvent systems, as well as the measured mole fraction solubilities in 1-propanol (x A sat ) 0.000 591), 2-propanol (x A sat ) 0.000 411), 1-butanol (x A sat ) 0.000 801), 2-butanol (x A sat ) 0.000 585), 2,2,4-trimethylpentane (x A sat ) 0.001 074), and cyclohexane (x A sat ) 0.001 553). Solubility data for the ninth binary solvent system was reported several years prior to the development of the combined NIBS/Redlich-Kister equation.…”
Section: Resultsmentioning
confidence: 99%
“…The various S i "curve-fit" parameters can be evaluated via least-squares analysis. Published papers (Zvaigzne et al, 1993;Zvaigzne and Acree, 1994; have reported the calculated S i parameters for anthracene dissolved in eight of the nine sub-binary solvent systems, as well as the measured mole fraction solubilities in 1-propanol (x A sat ) 0.000 591), 2-propanol (x A sat ) 0.000 411), 1-butanol (x A sat ) 0.000 801), 2-butanol (x A sat ) 0.000 585), 2,2,4-trimethylpentane (x A sat ) 0.001 074), and cyclohexane (x A sat ) 0.001 553). Solubility data for the ninth binary solvent system was reported several years prior to the development of the combined NIBS/Redlich-Kister equation.…”
Section: Resultsmentioning
confidence: 99%
“…The various S i "curve-fit" parameters can be evaluated via least-squares analysis. Published papers (Zvaigzne et al 1993;Zvaigzne and Acree, 1994;) have reported the calculated S i parameters for anthracene dissolved in the eight sub-binary solvent systems, as well as the measured mole fraction solubilities in 1-propanol (x A sat ) 0.000 591), 2-propanol (x A sat ) 0.000 411), 1-butanol (x A sat ) 0.000 801), 2-butanol (x A sat ) 0.000 585), and cyclohexane (x A sat ) 0.001 553). Numerical values of the S i parameters have been tabulated in Table 2 for convenience.…”
Section: Resultsmentioning
confidence: 99%
“…The model constants of eqs 1 and 2 along with the experimental solubility of anthracene in monosolvents were employed to calculate the solubilities. All calculated C m Sat solubilities were compared with the corresponding experimental values, and the mean deviation (MD) was calculated as an accuracy criterion by: (3) in which N is the number of data points in each set. Tables 1 and 2 list the experimental solubilities of anthracene, along with the back-calculated solubilities using eqs 1 and 2 and the densities of the respective saturated solutions.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The calculated model constants and MD values were computed and listed in Table 3 in which the solubilities were calculated with a reasonable MD (5.1 %), and this finding is in agreement with previous results. [3][4][5] Literature Cited…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation